Abordagens corporais: recurso transformador na formação do terapeuta ocupacional - Silva, Meire Luci da [UNESP]; Gregorutti, Carolina Cangemi [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2014)
The objective of this study was to discuss the teaching-learning process of corporal approaches in the Occupational Therapy fi eld. The informations were collected during the classes, in the body approaches matter, administered in the fourth period of the graduate program in Occupational Therapy of the Universidade Estadual Paulista, through focus groups conducted at the end of all twelve-face meetings with classes of four hours each. The study was realized by forty students enrolled in the discipline. All meetings were fi lmed, which allowed the full transcript and analysis of the students reports. The speeches analysis consisted of content analysis and categories creation. The results indicated to the perception of the thematic discussed during the meetings enabled the student to experience and build critical thinking about what is proper the client, and through a holistic approach, about what is guiding the potency of the Occupational Therapy process. The body approaches are considered a feature powerfull transformer in the teaching-learning of occupational therapy as an investigative and formative activity in the understandings’ construction of the professional practice of occupational therapists in situations of uniqueness, complexity, uncertainty and confl ict in the value process.

O objetivo deste estudo foi discutir o processo de ensino-aprendizagem de abordagens corporais no campo da Terapia Ocupacional. Os dados foram coletados durante a disciplina em abordagens corporais ministrada no curso de graduação em Terapia Ocupacional da Universidade Estadual Paulista, por meio de grupos focais realizados ao fi nal de doze encontros presenciais com quatro horas/aula cada. O estudo foi desenvolvido com quarenta discentes matriculados na disciplina. Todos os encontros foram fi lmados e transcritos na íntegra, sendo os relatos analisados através do método análise de conteúdo e criação de categorias. Os resultados apontaram para percepção de que as temáticas discutidas durante os encontros possibilitaram ao discente vivenciar e construir um pensamento crítico a respeito daquilo que é próprio do cliente aproximando-o, por meio de uma abordagem holística, daquilo que é potência norteadora do processo em Terapia Ocupacional. As abordagens corporais são consideradas um recurso transformador e potente no processo ensino-aprendizagem da Terapia Ocupacional e como atividade formativa investigativa na construção das compreensões da prática profi ssional do terapeuta ocupacional em situações de singularidade, complexidade, incerteza e confl ito de valores.
Corporal approaches: transformer action in training of the occupational therapist
Keywords: abordagens corporais; ensino-aprendizagem; Terapia Ocupacional